Management of Habitual Patellar Dislocation in Pediatrics - Sananta, Panji -; Churie Tanjaya, Ade; Fuzianingsih, Eka Noviya (Universitas Muhammadiyah Surabaya, 2025)
Habitual patellar dislocation occurs when the knee is bent and returns to its usual position when straightened. Habitual patella dislocation is 13.5 per 100,000 in children under 13 and 147.7 per 100,000 in children 14–18. This review aims to present a comprehensive and complete literature on the management of habitual dislocation of the patella so that appropriate therapy can be obtained. A complete literature review was used in this investigation. Source search databases are PubMed, Science Direct, and Google Scholar. The literature study shows that habitual patellar dislocation in children is infrequent. Stability requires bone and connective tissue that match the patellofemoral joint. Patella alta, torsional, angular, trochlear dysplasia, muscular anomalies, ligamentous laxity, or ligament damage can produce lateral patellar habitual instability. The quadriceps muscle drags laterally to the limb's mechanical axis. Clinical children with recurrent patellar dislocation may experience a sudden dislocation that